Effects of Isorhamnetin in Human Amniotic Epithelial Stem Cells in vitro and Its Cardioprotective Effects in vivo - Aonuma, Kazuhiro; Ferdousi, Farhana; Xu, DongZhu; Tominaga, Kenichi; Isoda, Hiroko (Frontiers in Cell and Developmental Biology, 2020)
Cardiac hypertrophy and fibrosis are major pathophysiologic disorders that lead to serious cardiovascular diseases (CVDs), such as heart failure and arrhythmia. It is well known that transforming growth factor β (TGFβ) signaling pathways play a major role in the proliferation of cardiac hypertrophy and fibrosis, which is mainly stimulated by angiotensin II (AgII). This study aimed to investigate the cardioprotective potential of isorhamnetin (ISO) in human amniotic epithelial stem cells (hAESCs) through global gene expression analysis and to confirm its beneficial effects on cardiac hypertrophy and fibrosis in the AgII-induced in vivo model. In vitro, biological processes including TGFβ, collagen-related functions, and inflammatory processes were significantly suppressed in ISO pretreated hAESCs. In vivo, continuous AgII infusion using an osmotic pump induced significant pathological fibrosis and myocardial hypertrophy, which were remarkably suppressed by ISO pretreatment. ISO was found to reverse the enhanced TGFβ and Collagen type I alpha 1 mRNA expression induced by AgII exposure, which causes cardiovascular remodeling in ventricular tissue. These findings indicate that ISO could be a potential agent against cardiac hypertrophy and fibrosis.